Jabreshwar Mahadev Temple seen from Jabreshwar Gali - Ghosh, Ayan (2023)
The location of Banganga Tank and Walkeshwar is at the foot of the western face of Malabar Hill, on breaking point of the Arabian Sea. The stone paved Jabreshwar Gali is one of two alleys leading to Banganga Tank from Walkeshwar Road running along the ridge of Malabar Hill. The most prominent temple in Jabreshwar gali is the eponymous Jabreshwar Temple, built in the 1840s by Nathuram Ramdas, father of a leading Bombay merchant, Sir Mangaldas Nathubhai.